2010
DOI: 10.1080/00221309.2010.484449
|View full text |Cite
|
Sign up to set email alerts
|

Delay Discounting of Different Commodities

Abstract: When outcomes are delayed, their value is decreased. Delay discounting is a much-studied topic because it is correlated with certain disorders (e.g., pathological gambling). The present study attempts to determine how people would delay discount a number of different commodities, ranging from money to dating partners to federal education legislation. Participants completed delay discounting tasks pertaining to 5 different commodities, with a different set of 5 commodities for 2 groups. Results showed that diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 14 publications
3
62
6
Order By: Relevance
“…A significant difference in the absolute value of this commodity in the present study was only observed in one of four potential instances (i.e., for k when participants were owed $1,000). Given that Equation 1 did not provide a particularly good fit for the present data, and the finding that rates of discounting differ depending on whether the questions concern hypothetical money that is owed or won (Weatherly, Derenne, & Terrell, 2010), it is difficult to determine how different the present results are from those reported by Beck and Triplett. In general, the finding that absolute values of k and AUC may vary across time suggests that studies of delay discounting may be most informative if they focus on relative differences rather than absolute differences.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…A significant difference in the absolute value of this commodity in the present study was only observed in one of four potential instances (i.e., for k when participants were owed $1,000). Given that Equation 1 did not provide a particularly good fit for the present data, and the finding that rates of discounting differ depending on whether the questions concern hypothetical money that is owed or won (Weatherly, Derenne, & Terrell, 2010), it is difficult to determine how different the present results are from those reported by Beck and Triplett. In general, the finding that absolute values of k and AUC may vary across time suggests that studies of delay discounting may be most informative if they focus on relative differences rather than absolute differences.…”
Section: Discussioncontrasting
confidence: 54%
“…First, we did not want to potentially exacerbate the cognitively demanding nature of the FITB method. Second, previous research (Weatherly, Terrell, & Derenne, 2010) had followed a similar procedure. The commodities in Set A were winning $1,000, winning $100,000, 100 packs of cigarettes, obtaining the ideal body image through exercise and dieting, and finding the perfect dating partner through a dating service.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was proposed to explain previous research findings from studies of human response to delayed gratification. These findings showed that rewards or reinforcers that drive our behaviors tend to lose their value if the access to them is far in future (Weatherly, Terrell, & Derenne, 2010). Thus, a smaller more immediate reinforcer value may exceed the value of a larger reinforcer that is distant in the future resulting in impulsive behavior (Gullo & Potenza, 2014).…”
Section: The Hot/cool System Modelmentioning
confidence: 98%
“…Others have focused on impulsivity as a personality trait, a theme particularly researched in the area of out-of-control consumption behaviors such as drug addiction, smoking, gambling, alcoholism, and so on (Madden & Bickel, 2009); but also in discounting's more prosaic connection with numerical ability (Peters, Slovic, Västfjäll, & Mertz, 2008). Focusing on the situation (i.e., the kind of commodity being discounted) rather than the person, other researchers have examined the extent to which discounting is domain specific in normal (i.e., non-addicted) people who nonetheless also experience the temptations of consumption (Hardisty & Weber, 2009;Tsukayama & Duckworth, 2010;Weatherly, Terrell, & Derenne, 2010). Yet others have examined factors that lead people to behave more impulsively across disconnected domains: e.g., Wilson and Daly (2004) found that seeing pictures of the faces of attractive women induced men to discount money more steeply than if the faces were unattractive.…”
mentioning
confidence: 99%